BENIDIR Mohamed - HOUSSOU Hind; BOUZEBDA AFRI Farida; BOUZEBDA Zoubir (Agricultural Research Communication Centre, 2020)
This study was carried out at National Haras of Tiaret (west of Algeria) to understand and to compare the normal sexual behavior and libido of stallions (Arabian vs Barb) while mounting a mare in estrus. Eighty-four stallions were divided into two groups from 5 to 24 years of age (n=47 Arabian; n=37 Barb). Results revealed significant differences between Arabian and Barb stallion: in sniffing(p<0.001), libido score (p<0.05), flehmen response (p<0.05), time to first mount with erection (p<0.05), number of mounts to ejaculation (p<0.05) and mount time for ejaculatory (p<0.01). These stallions were exactly tested in the same place and conditions allowed us to discard any side effects due to animal management or any other confounding bias. Our study provided us the knowledge of sexual behavior under Algerian environmental conditions and the distinction between Arabian and Barb stallion in their sexual behavior expression
Evaluation of sexual behavior of stallion (Arabian versus Barb) during breeding season in Algeria